2007
DOI: 10.1016/j.bone.2007.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Hip structural geometry in old and old-old age: Similarities and differences between men and women

Abstract: Introduction-Changes in hip structure and geometry during aging contribute to decreased bone strength. Little is known, however, about these characteristics at advanced age, when fragility fractures are common. We examined hip structural geometry in men and women of old (72-84 years) and old-old (85-96 years) age to determine (1) gender differences; 2) whether or not these differences are consistent with the increased occurrence of hip fracture in elderly women, compared to men; and (3) whether or not gender-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 61 publications
4
52
1
2
Order By: Relevance
“…Four studies reported increased rates of cartilage loss in women [13,15,17,21], one study reported an increasing incidence of osteophytes in women, compared to men, older than 60 years [23], and another study reported increased varus/valgus laxity in women [47]. There were several anatomic differences found between hips of men and women in the literature reviewed, including bone size [7,30,38], femoral offset [38,51], proximal femoral shape [42,51], and trabecular patterns [51].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies reported increased rates of cartilage loss in women [13,15,17,21], one study reported an increasing incidence of osteophytes in women, compared to men, older than 60 years [23], and another study reported increased varus/valgus laxity in women [47]. There were several anatomic differences found between hips of men and women in the literature reviewed, including bone size [7,30,38], femoral offset [38,51], proximal femoral shape [42,51], and trabecular patterns [51].…”
Section: Resultsmentioning
confidence: 99%
“…Much as with the anatomy of the knee, several forensic analyses have suggested there are anatomic differences in hips between the genders [38,42,43,48,51]. These include bone size, femoral offset, proximal femoral shape, bone mineral content, and trabecular patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The method has been compared favourably to volumetric qualitative computed tomography (QCT) (Prevrhal et al, 2008) and enables DXA-derived data to be expressed in ways that are more mechanically interpretable so that the geometric properties that underlie the prognostic value of BMD measurements can provide critical insights into bone strength. The results from HSA have been used in studies as indices of bone strength to predict hip fracture (Faulkner et al, 2006;Leslie et al, 2009), to inform about sexual and ethnicity dimorphism in bone strength and fracture (Wang et al, 2005;Yates et al, 2007), evaluate associations with exercise during growth (Janz et al, 2007) and assess the effects of weight-bearing exercise interventions on bone (Petit et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Згідно з даними літературних джерел, незалежним чинником переломів ПВ СК є вік [2,19]. При аналізі вікових особливостей геометрії ПВ СК у чоловіків на-ми встановлено вірогідно менші показники довжи-ни осі та шийки стегнової кістки, відстані «головка -вертлюг» та міжвертлюгової відстані, а також шири-ни основи головки у хворих із внутрішньосуглобови-ми ПСК віком 70-89 років порівняно з віковою гру-пою 50-69 років (табл.…”
Section: результати дослідження та їх обговоренняunclassified